Achnanthidium palmeti (Bacillariophyta, Achnanthidiaceae), a new freshwater species from Réunion Island - Gassiole, Gilles; Cohu, René Le; Coste, Michel (Phytotaxa, 2013)
Recent survey of the epilithic diatoms in the running waters of Réunion Island led to the discovery of a new species of Achnanthidium. Achnanthidium palmeti sp. nov. belongs to the group of Achnanthidium taxa with terminal raphe fissures curved to the same side of the valve. The new species differs from other taxa in this group by a higher stria density and the areolae morphology along the axial area; moreover, apart from Achnanthidium latecephalum H. Kobayasi, A. palmeti sp. nov. is the only species having raphe vestiges. The new species was found in oligotrophic waters with very low conductivity and circumneutral pH.